Anti‐melanogenic effects of extracellular vesicles derived from plant leaves and stems in mouse melanoma cells and human healthy skin. Issue 1 (18th December 2019) - Lee, Ruri; Ko, Hae Ju; Kim, Kimin; Sohn, Yehjoo; Min, Seo Yun; Kim, Jeong Ah; Na, Dokyun; Yeon, Ju Hun
ABSTRACT: Consumer interest in cosmetic industry products that produce whitening effects has increased demand for agents that decrease melanin production. Many such anti‐melanogenic agents are associated with side effects, such as contact dermatitis and high toxicity, and also exhibit poor skin penetration. Considerable recent research has focused on plant‐derived products as alternatives to chemotherapeutic agents that possess fewer side effects. In the current study, we investigated the anti‐melanogenic effects of extracellular vesicles (EVs) extracted from leaves and stems of Dendropanax morbifera . Using spectrophotometric and biochemical approaches, we found that leaf‐derived extracellular vesicles (LEVs) and stem‐derived extracellular vesicles (SEVs) reduced melanin content and tyrosinase (TYR) activity in the B16BL6 mouse melanoma cell line in a concentration‐dependent manner. An electron microscopy analysis further confirmed that LEVs and SEVs induce a concentration‐dependent decrease in melanin content in melanoma cells. Both LEVs and SEVs exerted a greater whitening effect on melanoma cells than arbutin, used as a positive control, with LEVs producing the greater effect. Notably, neither LEVs nor SEVs induced significant cytotoxicity. We also examined the effects of plant‐derived EVs on the expression of tyrosinase‐related proteins (TRPs) in melanoma cells. LEVs inhibited expression of melanogenesis‐related genes and proteins, including microphthalmia‐associated transcription factor (MITF), TYR, TRP‐1 and TRP‐2. In a human epidermis model, LEVs exerted a stronger inhibitory effect on melanin production than arbutin. Collectively, our data suggest that LEVs from D. morbifera may be a novel candidate natural substance for use as an anti‐melanogenic agent in cosmeceutical formulations.